Innovations in investments and corporate finance - Hirschey, Mark; John, Kose; Makhija, Anil K. (Amsterdam: JAI, 2002)
The book covers 1. Valuation of internet companies: a survey of the evidence 2. Decisions in financial economics: an experimental study of discount rates. 3. Institutional ownership, information and liquidity. 4. Internal cash flows and corporate investment decisions. 5. Preferences on relative return: a potential explanation for some pricing anomalies. 6. Capital market efficiency and its implications for the investor: a case of a superior product mismarketed. 7. How different is the long-run performance of mergers in the telecommunications industry?
Includes bibliographical references.
osa 10/09/13
Loans
Keywords: Investments; Corporate finance